Transformative Impact of Artificial Intelligence on Healthcare - Pratik S. Kumbhar; Swapnali A. Salunkhe (Journal of Computer Based Parallel Programming, 2024)
Artificial Intelligence (AI) is transforming the healthcare industry by enhancing diagnostic accuracy, optimizing treatment plans, and improving patient care outcomes. This paper examines the impact of AI technologies, particularly Machine Learning (ML) and Natural Language Processing (NLP), in healthcare, focusing on critical areas such as medical imaging, drug discovery, and personalized medicine. AI’s integration with telemedicine and the Internet of Things (IoT) is also explored, illustrating how these advancements improve resource allocation and streamline healthcare delivery. The COVID-19 pandemic underscored AI’s importance, from predicting outbreaks to aiding vaccine development and distribution, highlighting its role in public health emergencies. Real-world applications, such as AI’s ability to analyze radiological images and assist in detecting diseases, demonstrate its precision and contribution to improving diagnostic processes. In drug discovery, AI accelerates the identification of potential therapies by analyzing extensive datasets, significantly reducing time and costs. Personalized medicine is another area where AI plays a crucial role, enabling the development of tailored treatment strategies based on individual patient data, leading to better health outcomes and more efficient use of healthcare resources. This paper also addresses ethical considerations, including fairness in AI algorithms, safeguarding patient data privacy, and ensuring transparency in AI-driven healthcare decisions. Overcoming these challenges is essential to fostering trust in AI technologies. Collaborative efforts among healthcare professionals, technologists, and data scientists must ensure that AI’s integration into healthcare is responsible and aligns with clinical priorities. This paper highlights AI’s potential to drive a more resilient, efficient, and patient-centered healthcare system in the future.